A review of research progress in the design history of everyday life - Hongying Jia (Heliyon)
The study of everyday life has garnered significant research attention in various disciplines. However, in the field of design history, the exploration of everyday life remains in its early stages. There is a need for further organization and analysis, as there is currently no comprehensive exposition on the overall research progress in this field. To address this gap, this paper employs bibliometric and knowledge graph methods to summarize the research progress in the design history of everyday life. By analyzing high-frequency keywords, thematic trends, citation networks, co-occurrence knowledge graphs, and burst keywords, we provide an objective evaluation of the development of the research perspective on everyday life in design history. The findings reveal an overall increasing trend in research efforts in the design history of everyday life, with a focus on Europe and America. The research in this field has evolved from philosophical explorations to disciplines such as history and anthropology, with interconnections between different directions. Prior to 2000, the emphasis was on the philosophical essence and fundamental theories of everyday life. From 2001 to 2010, there was a surge in psychological research and discussions on female topics within the design history of everyday life. In recent years, there has been a further expansion in the proportion of research on everyday life in the design history field, with more diverse dimensions of study. However, it is important to note that the research in the design history of everyday life is currently in a stage of conceptual understanding, with limited theoretical achievements. This paper not only provides a comprehensive overview of the current research progress but also presents an outlook on the research prospects in the design history of everyday life. It serves as a valuable resource for scholars and practitioners interested in advancing the understanding of the design history of everyday life.